Basiese grondslae as riglyne by die onderrig van Bybelkunde - Herman, Louis Thomas Ignatius (University of the Free State, 1976)
Abstract not available
Keywords: Bible study; Bible teaching; Biblical studies; Dissertation (M.A. (Biblical Studies))--University of the Free State, 1976